Prosody and Processing: Comprehension and Production of Topic-Comment and Subject-Predicate Structures in Brazilian Portuguese / Prosódia e processamento: compreensão e produção de estruturas de tópico e de sujeito no português brasileiro (Revista de Estudos da Linguagem, 2018)
Abstract: This paper explores the influence of prosody in the processes of comprehension and production of sentences in Brazilian Portuguese with topic-comment syntactic structure and sentences with subject-predicate syntactic structure, in active or passive voice. Three experimental activities were carried out, one production task and two comprehension tasks. Experiment 1 consisted of a perception task with the ABX technique, and it aimed to test if hearers recognize prosodic differences between topicalized Determinant Phrases (DPs) and DPs in subject position. Experiment 2 consisted of a sentence elicitation task with Cross-modal naming technique and it aimed to investigate whether Portuguese native speakers produce a subject-predicate structure or a topic-comment structure in contexts that favor the occurrence of these syntactic structures in speech. Experiment 3 consisted of a comprehension task with Self-paced listening and reading technique and it aimed to investigate whether prosodic characteristics of a DP, in topic or subject position, can guide hearers during the processing in order to distinguish between these two syntactic categories. From the comprehension/perception perspective, the results of the experiments 1 and 3 indicated that speakers recognize the prosodic differences between the topicalized DPs and the subject DPs, and use such characteristics during linguistic processing. From the production perspective, the results of experiment 2 revealed that speakers are able to produce sentences consistent with topic-comment and subject-predicate syntactic structures when the context favors the occurrence of one of them. Nevertheless, the results also reveal a preference for the subject-predicate structure over the topic-comment structure in BP.Keywords: prosody-syntax; topic-comment; subject-predicate.Resumo: Este trabalho investiga a influência da prosódia nos processos de compreensão e produção de sentenças com elementos topicalizados, do tipo tópico-comentário, e sentenças com a estrutura de sujeito-predicado, na voz ativa ou passiva, do Português Brasileiro. Aplicaram-se três atividades experimentais, uma tarefa de produção e duas de compreensão. O Experimento 1 consistiu em um teste de percepção com a técnica ABX, cujo objetivo foi testar se ouvintes reconhecem as diferenças prosódicas entre Determinant Phrases (DPs) topicalizados e DPs em posição de sujeito não topicalizado. O Experimento 2 consistiu em um teste de elicitação de frases com imagens do tipo Cross-modal naming, cujo objetivo foi investigar se em contextos que favorecem a ocorrência de estruturas de sujeito ou de estruturas topicalizadas, os falantes produzem frases consistentes com tais estruturas sintáticas. O Experimento 3 consistiu em uma tarefa de compreensão, com a técnica Self-paced listening and reading, cujo objetivo foi investigar se as características prosódicas de um DP, em posição de tópico ou de sujeito, conseguem guiar o processamento linguístico dos ouvintes na distinção entre essas duas categorias sintáticas. Na compreensão/percepção, os resultados dos experimentos indicaram que os falantes reconhecem as diferenças prosódicas entre os DPs topicalizados e os DPs em posição de sujeito, e utilizam tais características durante o processamento linguístico. Na produção, os resultados revelaram que os falantes produzem frases consistentes com estruturas sintáticas de tópico e de sujeito quando o contexto favorece o aparecimento delas, entretanto, apontam para uma preferência da estrutura de sujeito como default no PB.Palavras-chave: prosódia-sintaxe; tópico-comentário; sujeito-predicado.